FORMULASI PERMEN JELI EKSTRAK DAUN UBI JALAR (Ipomoea batatas L.) SEBAGAI SUPLEMEN MAKANAN - nesa agistia (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2014)
The research of jelly candy formulation of leaf extract of sweet potato concentration 2% as food suplement has been studied. The formulation consistof six formula with used gelatin as gel forming material. Gelatin concentration 6%, 8%, 10%, 12%, 14%, and 16% for each formula. The evaluationincluding organoleptic evaluation, panelists test, pH ,weight h omogenity, water rate, and fitochemistry test was been done for each formula. Theresult showed that formula 6 with gelatin consentration 16%, pH 6,22, and water rate 17% the best formula. The data from panelist test wereanalized by one way ANOVA SPSS 17 program, the result showed th at there was significant difference of elasticity, shape and colour for eachformula (p<0,05) and there was not significant difference of s mell and flavour for each formula (p>0,05). Formula 6 was the best formula, that wasnot significant different with jelly candy comparator (COMBI KIDÒjelly).